The relationship between CSR disclosure and accounting conservatism : The role of state ownership - Garanina, Tatiana; Kim, Oksana (JAI Press, 2023)
The literature has explored an association between corporate social responsibility (CSR) disclosure and accounting conservatism. This paper investigates how state ownership moderates this relationship in the context of the emerging Russian economy. Using a sample of 223 publicly listed Russian companies for the period of 2012–2017, we find that companies with higher CSR disclosure tend to have more conservative financial reporting practices. We observe, however, that state ownership has a negative moderating effect on this association, in line with agency theory. Moreover, we explore the unique structure of Russian companies’ state ownership, whereby public companies often have a combination of federal, regional, and municipal state ownership, the outcome of privatization reform. We find that federal state ownership alone or in combination with regional or municipal levels of state ownership has a significantly negative impact on the CSR disclosure–accounting conservatism association. We find no evidence that a regional or municipal level of state ownership, a combination of regional and municipal levels of state ownership, or a combination of all three levels has an impact on the association between CSR disclosure and reporting conservatism. We address the recent call for a contextualized approach that focuses on institutional, legal, and cultural features of different economies to advance our knowledge of the antecedents of CSR disclosure, its association with reporting quality, and the factors that moderate it.
Keywords: CSR disclosure; State ownership; Accounting conservatism; Accounting aggressiveness; Russian public companies; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|